Development of HVDC system-level mechanical circuit breaker model - Liu, Siyuan; Popov, Marjan (International journal of electrical power & energy systems, 2018)
•Robust System model of a mechanical DC circuit breaker with current injection circuit.•Performance of the model under different circuit conditions.•Detailed explanation of the energy absorption during DC current interruption and time to interrupt the current. The main goal of the paper is the modelling of the mechanical direct current circuit breaker (DC CB) with active current injection that includes different circuit breaker characteristics. System level models provide adequate representation of the circuit breakers for system analysis studies. The performance characteristics of the DC CB in those proposed models replicate the ones of the devices in practice. The developed mechanical circuit breaker model is realized for a 320 kV demonstration circuit in PSCAD environment and its limitations and robustness are analyzed. The performance of the model is investigated by different cases. The obtained results show that the DC CB model can be used with full success for both to simulate DC fault interruptions and to be used for different protection studies.